Wieś polska w perspektywie stulecia. Refleksje rocznicowe 1918-2018 - Wieruszewska-Adamczyk, Maria (Zeszyty Wiejskie, 2018)
Disintegration of villages was the important process of social change in Poland during the Century of 1918-2018 years. It run nor in the linear nor in the one directed manner however. The process of disintegration of rural community was not universal one on the territory of Poland. It also has no unilateral effects during the period of 1918-2018. The consolidation, connection, affiliation of economic, social and cultural domain of the State were the most characteristic trends of the period of the twenty years before of the Second World War. The rapid changes in the earlier process of integration of rural social community took over during The Second World War and next years implemented by new policy in Poland after 1945 year. The new rules of transformation intensify the discussion connected with problems of village and agriculture after 1989 year. Slowly, step by step, there were come into sight the new symptoms of the reintegration process of local village community after 30 years of transformation.